Chatting in a mobile chamber: effects of instant messenger use on tolerance toward political misinformation among South Koreans. Issue 6 (1st November 2020) - Gill, Hyungjin; Rojas, Hernando
ABSTRACT: Amid growing scholarly interest in identifying potential explanations for the persistence of fake news from an international context, this study explores the relationship between instant messaging (IM) app use and attitudes regarding political falsehoods. Using a 2018 survey from a nationally representative sample of South Korean adults, path analysis reveals that network homogeneity indirectly predicts citizens' tolerant attitudes toward misinformation, through frequency of real-time chat app use for political communication. This process is moderated by the perceptions we hold of our political discussion partners. These results further previous understanding of IM as an intimate political communication channel that may foster consonant belief systems. Implications of our findings are discussed.